2014
DOI: 10.1007/s11302-014-9439-y
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia

Abstract: Irritable bowel syndrome (IBS) and inflammatory bowel disease often display visceral hypersensitivity. Visceral nociceptors after inflammatory stimulation generate afferent nerve impulses through dorsal root ganglia (DRG) transmitting to the central nervous system. ATP and its activatedpurinergic 2X 7 (P2X 7 ) receptor play an important role in the transmission of nociceptive signal. Purinergic signaling is involved in the sensory transmission of visceral pain. Moxibustion is a therapy applying ignited mugwort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…P2XRs seem to be involved in visceral pain and are directly involved in the pathophysiology of IBD, with regard to intestinal inflammation but also to dysmotility and pain. 36 In animals, several studies have also evidenced P2XRs involvement in visceral pain [37][38][39] and in accordance to our findings, in post-infectious CHS, 6 even if, in our model, the direct involvement of P2XRs in CHS need to be prove using P2XRs knockout mice or P2XRs antagonists.…”
Section: Discussionsupporting
confidence: 90%
“…P2XRs seem to be involved in visceral pain and are directly involved in the pathophysiology of IBD, with regard to intestinal inflammation but also to dysmotility and pain. 36 In animals, several studies have also evidenced P2XRs involvement in visceral pain [37][38][39] and in accordance to our findings, in post-infectious CHS, 6 even if, in our model, the direct involvement of P2XRs in CHS need to be prove using P2XRs knockout mice or P2XRs antagonists.…”
Section: Discussionsupporting
confidence: 90%
“…Visceral hypersensitivity is often seen in IBS. It has been suggested that P2X7R of rat dorsal root ganglia may play a role in the transmission of the nociceptive signal (Liu et al, 2015). Emerging evidence suggests that electroacupuncture may downregulate the expression of the P2X3R and ease the sensitivity to IBS visceral pain (Weng et al, 2015).…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%
“…Recent studies suggest that neuron-microglia interaction mediated by purinergic receptors, and subsequently by chemokine fractalkine (FKN) and its sole receptor CX3C chemokine receptor 1 (CX3CR1), plays a pivotal role in nociceptive signal transmission [9]. In addition, it was reported that ATP-gated purinergic receptor P2X7 of the dorsal root ganglia (DRG) was involved in the analgesia effect of moxibustion in rats with chronic visceral inflammatory pain [15]. ATP and P2X3 receptor in DRGs and the spinal cord were implicated in the pain relief of electroacupuncture (EA) in rats with neuropathic pain [16,17].…”
Section: Y H Gao and Cw LI Contributed Equally To This Workmentioning
confidence: 99%